Impact of Social Support on the Standard of Living and Psychological Well-Being of Women Exposed to Violent Conflicts - Zuhumben Beatrice Paul; Joy Ojoma Nyam (Department of Guidance and Counseling, FIP, Undiksha, 2026)
Women in Plateau State, Nigeria, have experienced prolonged exposure to conflict caused by the Boko Haram insurgency, Fulani herder attacks, and ethno-religious violence, resulting in displacement, trauma, and economic vulnerability. Although humanitarian assistance has been provided, evidence-based psychosocial interventions remain limited. This quasi-experimental study evaluated the effectiveness of social support interventions on psychological well-being and standard of living among conflict-affected women in Plateau State Internally Displaced Persons (IDP) camps. A pretest-posttest control group design was employed with 80 women (aged 18-60 years) randomly assigned to two groups: social support intervention (n=40) and control (n=40). The intervention was delivered over 12 weeks. Psychological well-being was measured using the Ryff Psychological Well-Being Scale, and standard of living was assessed using a validated Standard of Living Index. Data were analyzed using ANCOVA and independent t-tests. The social support intervention produced significant improvements compared to controls. The social support group demonstrated significant improvements in psychological well-being (F=52.18, p<0.001, eta-squared=0.42) and moderate gains in standard of living (F=28.45, p<0.001, eta-squared=0.28). Social support strongly influences psychological well-being, particularly autonomy, environmental mastery, and positive relationships with others. This intervention is highly effective in improving psychological well-being and moderately effective in enhancing the living standards of conflict-affected women. These findings support the integration of structured social support programs into humanitarian responses in Nigeria and similar post-conflict settings.